2016
DOI: 10.1111/nmo.12813
|View full text |Cite
|
Sign up to set email alerts
|

The association between systemic sclerosis disease manifestations and esophageal high‐resolution manometry parameters

Abstract: Background/Aims We aimed to evaluate the associations between SSc-related systemic manifestations and esophageal function using high-resolution manometry (HRM). Methods Patients with SSc that had undergone HRM between 1/2004 and 9/2014 were identified and HRMs were analyzed according to the Chicago Classification. Clinical characteristics were identified via retrospective chart review and compared among motility diagnoses while adjusting for age, gender, race, and SSc-disease duration. Results 79 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 48 publications
4
60
0
8
Order By: Relevance
“…Consistent with the results of the majority of studies, the frequency and intensity of GI symptoms reported on questionnaires did not associate with SSc disease stage in our patient cohort (Table ). The discrepancy between questionnaire data and pathological findings on HRM testing might be explained by reduced esophageal sensitivity, although the results of previous studies yielded mixed results .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the results of the majority of studies, the frequency and intensity of GI symptoms reported on questionnaires did not associate with SSc disease stage in our patient cohort (Table ). The discrepancy between questionnaire data and pathological findings on HRM testing might be explained by reduced esophageal sensitivity, although the results of previous studies yielded mixed results .…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, classification of SSc has evolved and disease groups in previous studies are not necessarily comparable to current investigations. To date, three HRM studies have documented the association of esophageal motility assessed by SWS with SSc disease activity . A small prospective study from our group focused on the treatment of reflux disease in 14 SSc patients, and two recent clinical series showed a link between esophageal motility and lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Other studies have suggested that IEM is closely associated with systematic diseases, including systemic sclerosis and chagas disease. [7][8][9] However, a recent study reported that there was no significant relationship between minor peristaltic disorders and symptoms. Moreover, minor disorders of peristalsis are unaffected by the management.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Chicago Classification v3.0, IEM is a manometric diagnosis in which the Integrated Residual Pressure (IRP) is less than 15 mm Hg, but ≥50% of swallows are either weak or failed (Distal Contractile Index [DCI] is ≤450 mm Hg) . IEM has been shown to be a possible pathophysiologic mechanism in patients with otherwise unexplained dysphagia and various series report an increase in the prevalence of IEM in patients with systemic sclerosis and Parkinson's disease …”
Section: Introductionmentioning
confidence: 99%